TEACHERS’ STRATEGIES IN TEACHING ABLUTION AND PRAYER TO STUDENTS WITH MULTIPLE DISABILITIES - Efendi, Sofian; Maryam; Khabibah, Lumngatul; Mudawamah, Ittikhatul; Muryani, Julia; Kurniawati, Intan (STKIP Citra Bakti, 2026)
Teaching ablution and prayer to students with multiple disabilities, particularly those with hearing, speech, and intellectual impairments, requires learning strategies that are adjusted to the characteristics and needs of the learners. Limitations in communication and cognitive abilities become significant challenges in understanding and practicing religious activities properly. This study aims to describe the learning strategies implemented by teachers and their role in supporting students’ understanding of ablution and prayer materials. The study employed a descriptive qualitative approach involving junior secondary students in a special school. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that learning becomes more effective through direct practice conducted gradually and repeatedly, supported by visual media in the form of instructional videos. These strategies assist students in understanding and practicing the sequence of ablution and prayer movements according to their individual abilities. In addition, communication barriers were identified due to differences in the use of sign language between the home and school environments. Social interaction and students’ level of independence were also found to influence the learning process. Therefore, adaptive, visual, and practice-based learning strategies play an important role in supporting Islamic Religious Education for students with multiple disabilities.